Developing the SMART-RISK System to Enhance Internal Oversight Governance in Higher Education - Harris Pinagaran Nasution; Ferry Fachrizal; Isni Khairina; Prisca Caesa Moneteringtyas (International Journal of Multidisciplinary Sciences and Arts, 2026)
Risk management has become a strategic component of public sector governance, including higher education institutions, to support accountability and effective internal oversight. Nevertheless, many Indonesian higher education institutions still rely on manual and fragmented risk management practices, leading to inconsistent documentation, limited monitoring, and weak risk-based decision making. This study aims to design and develop a web-based integrated risk management information system, namely SMART-RISK, to enhance the effectiveness of internal oversight at Politeknik Negeri Medan. The research employed a Research and Development (R&D) approach using the 4D model, which consists of define, design, development, and dissemination stages. Data were collected through a literature review and user perception questionnaires involving 18 institutional work units and analyzed descriptively. The results show that SMART-RISK successfully integrates core risk management processes, including risk identification, assessment, prioritization, monitoring, and reporting within a centralized web-based platform. The system is equipped with a risk dashboard and role-based access control to support data security, accountability, and ease of use. Initial user evaluations indicate positive acceptance of the system’s functionality and interface, suggesting that the system is suitable for institutional risk governance. This study concludes that SMART-RISK has strong potential as a digital solution to support risk-based internal oversight in vocational higher education. Further research is required to implement the system in full operational settings and to empirically assess its impact on risk management maturity and institutional performance.